El siglo XX mexicano : la bola, la Revolución, la guerra civil - Miguel Rodriguez (Amnis)
Mexico’s 20th century is generally linked to the myth of the « Revolution » (term used by Luis Cabrera, since its beginnings in 1911). This paper provides us information on the revolutionary process and on the debates about its evolution and its « crisis », mostly after the 40's. The paper also revises the positive connotations of the word « revolution », used by its protagonists, by thinkers and as by historiography, in different ways of « civil war » and of « la bola », popular name used in 19th century's Mexico (by the novelist Emilio Rabasa ) to evoke popular and unorganized uprisings.